Human papillomavirus in cervical cancer and oropharyngeal cancer: One cause, two diseases. Issue 12 (27th March 2017) - Berman, Tara A.; Schiller, John T.
Abstract : Human papillomavirus (HPV) causes greater than 5% of cancers worldwide, including all cervical cancers and an alarmingly increasing proportion of oropharyngeal cancers (OPCs). Despite markedly reduced cervical cancer incidence in industrialized nations with organized screening programs, cervical cancer remains the second most common cause of death from cancer in women worldwide, as developing countries lack resources for universal, high‐quality screening. In the United States, HPV‐related OPC is only 1 of 5 cancers with a rising incidence since 1975 and now has taken over the cervix as the most common site of HPV‐related cancer. Similar trends follow throughout North America and Europe. The need for early detection and prevention is paramount. Despite the common etiologic role of HPV in the development of cervical cancer and HPV‐associated OPC, great disparity exists between incidence, screening modalities (or lack thereof), treatment, and prevention in these 2 very distinct cohorts. These differences in cervical cancer and HPV‐associated OPC and their impact are discussed here. Cancer 2017;123:2219–2229. © 2017 American Cancer Society . Abstract : Despite the common etiologic role of human papillomavirus in the development of cervical cancer and human papillomavirus‐associated oropharyngeal cancer, great differences exist in the incidence, screening, treatment, and prevention of these 2 very distinct cohorts. Here, these differences and their impact are discussed.